FOSTERING DIFFERENTIATED INSTRUCTION BY SCHOOL-BASED COMMUNITY SERVICE TO CONTRIBUTE TEACHERS’ PROFESSIONAL DEVELOPMENT - Aliva Rosdiana; Haryanto Haryanto; Olyvia Revalita Candraloka; Hayu Dian Yulistianti (LPPM ITB AAS Indonesia Surakarta, 2024)
Differentiated instruction is a new paradigm curriculum especially conducted by teachers of MA Miftahul Huda Bulungan Jepara. Curriculum is innovated to essence independent learning conducted by teachers and students in learning process. School-based community has several opportunities for teachers and students to be innovative in implementing the Merdeka Curriculum Program. This school based-community service activity is aimed at providing knowledge to teachers and stakeholders at MA Miftahul Huda Bulungan Jepara, and training teachers and stakeholders at MA Miftahul Huda Bulungan Jepara by fostering differentiated instruction in order to contribute teachers’ professional development. The activity employed includes expository, Q&A, demonstration, and discussion. The result of school-based community service activity after getting post-test conducted to 17 teachers and stakeholders is that 72% teachers as participants claimed having knowledge and skills improved. Besides, the score average of post-test given was higher than the average score of pre-test of 49. Most teachers expected a sustainable mentoring program as the follow-up of school-based community. Keywords: differentiated instruction; school-based community service; MA Miftahul Huda Bulungan Jepara; Merdeka Curriculum Program